Litho‐mineralogy, geochemistry, and chronology for the genesis of the Kamust sandstone‐hosted uranium deposit, Junggar Basin, NW China. Issue 4 (28th December 2021) - Huang, Shaohua; Qin, Mingkuan; Liu, Zhangyue; He, Zhongbo; Geng, Yingying
Abstract : The Kamust sandstone‐hosted uranium deposit was recently discovered within the Middle Jurassic Toutunhe Formation of the eastern Junggar Basin. In this study, polarizing microscope and scanning electron microscope observation, electron microprobe analysis, and laser ablation inductively coupled plasma mass spectrometry measurement were carried out to define the petrology, mineralogy, and geochemistry of these sandstone‐hosted uranium ores. In addition, sulphur isotope signatures for the associated ore‐stage pyrites and the ore‐forming age were determined. The results show that the mineralized sandstones, which exhibit excellent reducibility with abundant organic matter and pyrites, are characterized by the secondary accumulation of uranium and are slightly enriched in rare earth elements (REE) and light REE (LREE). The uranium deposits are mainly composed of a large amount of uraninite, followed by some coffinites and uranium‐bearing titanium minerals and very few sorptive uranium‐bearing materials. Uranium minerals primarily exist within the interior and edge of clastic particles in colloidal, dispersed, and vein form, and some are closely interweaved with the colloidal and framboidal pyrites and carbonaceous detritus. Both uraninite and coffinite are strongly enriched in REE and LREE, as determined by in situ trace element measurements. Moreover, the δ 34 S values of the associated ore‐stage pyrites mostly range from −41.66 to −19.33‰, indicating biological origin, and light 32 S demonstrates the relatively low‐temperature and open‐system mineralization processes related to the microbial anaerobic action on the organic matter. One of the δ 34 S values (6.88‰) is possibly caused by Rayleigh isotope fractionation due to the utilization of residual heavy 34 S in the relatively later closed‐like mineralization system. The ore‐reforming ages of 27 ± 3.2 Ma, 22.4 ± 3.9 Ma, and 21.3 ± 2.3 Ma were obtained by U–Pb isotopic dating combined with U–Ra balance correction, corresponding to the rapid uplift event caused by the remote effect of the collision between the Indian and Eurasian plates at the end of the Palaeogene. In conjunction with the tectonic–sedimentary evolution of the study region, a four‐stage ore‐forming model for the Middle Jurassic Toutunhe Formation is preliminarily constructed: ① Development of ore‐bearing strata, ② initiation of the mineralization stage from the Late Jurassic to the Early Cretaceous, ③ deep burial by lacustrine and flood mudstone from the Cretaceous to the Palaeogene, and ④ the superimposed ore‐forming stage during the Neogene. These research results provide significant benefits for further uranium prospecting and in situ leach process mining in this basin. Abstract : Occurrence, geochemistry, and chronology for the ores of the Kamust sandstone‐hosted uranium deposit.